THE PRINCIPLE OF SOCIAL JUSTICE AS THE LAW - Brian Amy Prastyo (Jurnal IUS Kajian Hukum dan Keadilan, 2013)
The term of “social justice” has mentioned explicitly in Pancasila. As the nation philosophical base, every Indonesian citizen may interpret the meaning of this term. Interpretation of every citizen may be various caused by each personal have their own way of thinking. This article offered a picture of how the “social justice” term could be interpret in 4 points of view, that are; Indonesianist, liberalist, Islamic and post modernist point of view. Furthermore this article will shows basic similarity among four ideas above concerning “social justice” so that we could see the harmony among them in interpreting “social justice” term. In the end will be described how “social justice” term embraced as a principle and normatively functioned. That is as a guidance to state rights and obligations which in certain situation could hold stronger power than a valid regulation. Keywords: Justice Theory, Legal Positivism, Pancasila, Social Justice, Basic Right.Abstrak: